Adsorption and electrooxidation of DNA at glassy carbon paste electrodes - Pedano, Maria Laura (2010)
This work reports the study of the adsorption and electrooxidation of nucleic acids on glassy carbon paste electrodes (GCPE) by using chronopotentiometric stripping analysis. The influence of electrochemical pretreatments, binder content, supporting electrolyte, accumulation potential, and time on the adsorption and further electrooxidation of oligo(dG)21 is discussed. The adsorption behavior of double stranded calf thymus DNA (dsDNA) on GCPE is also evaluated. Trace (ppb) levels of oligo(dG)21 and (ppm) levels of dsDNA can be readily detected following short accumulation periods, with detection limits of 21 ppb and 200 ppb for oligo(dG)21 and dsDNA, respectively. The confined DNA layer demonstrated to be stable in air, in 0.200M acetate buffer pH 5.00, and in 0.020M phosphate buffer pH 7.40+0.50M NaCl.